SWOT analysis of fire insurance product marketing strategy at PT Chubb Life Insurance Indonesia Medan Branch: An Islamic perspective - Romadhon , Fauzi Ahmad; Rahma, Tri Inda Fadhila; Syahriza, Rahmi (Journal of Islamic Economics Lariba, 2024)
IntroductionIndonesian people are familiar with and use many sharia insurance products. However, research specifically discussing fire insurance products is still limited.ObjectivesThis study carries out a SWOT analysis of fire insurance products from the marketing strategy aspect and Islamic perspective.MethodThis study used a quantitative approach with a sample of PT. Chubb Life Insurance (Persero) Medan Branch, Indonesia. Data collection was carried out using interviews and questionnaires. This study uses SWOT Analysis to evaluate internal and external factors that influence a company to identify strengths and weaknesses.ResultsThe research results show that the strengths of PT. Chubb Life Insurance were in its principles that are not usury, its brand is strong and its policies and claims services are well served. The opportunity can be found around office buildings that requires fire insurance. The weaknesses faced are low market share and human resources. The threat is the large number of competing companies that have similar products and the public's lack of understanding about insurance.ImplicationsThis study shows a strong internal position and indicates that the company responded well to existing opportunities and avoided threats in the market.Originality/NoveltyThis study contributes to the study of fire insurance as part of Islamic insurance in Indonesia.